Ventilated cladding systems: structural and drainability performance criteria - Silva, Luiz Fernando Batista da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2018)
Cladding systems have significant effect on the performance and durability of building façades, contributing to the building watertightness, property valuation, aesthetic finishing, and decoration. Non-adherent cladding, also named rainscreen cladding or ventilated cladding, is currently used in residential and commercial buildings, new constructions, or retrofit operations, and it is considered an efficient measure to improve the moisture safety of building envelopes. Therefore, the absence of Brazilian normalization to ventilated cladding systems is one of the difficulties limiting its increased local application. In Brazil, a technical standard, NBR 15575, parts 1–6, (2013), establish the general performance requirements and test methods to evaluate residential building systems including structure, wall, floor, coverage, and hydraulic installation. However, this standard cannot be integrally applied to the cladding systems because it was developed considering the vertical wall system as a whole. In this study, we propose the criteria and test methods for assessing ventilated cladding systems while taking into account the structural safety (wind loads resistance, hard and soft impact resistance) and drainability requirements. The following activities are performed: literature review, practical case study, and tests on prototypes for validation of the proposal. The tests allow verification of the feasibility of the criteria and tests methods proposed. In addition, the proposal makes it possible to guide design, construction, and maintenance needs, thereby inducing the growth of this technology in Brazil.